Differentiating between pathological demand avoidance and antisocial personality disorder: a case study. Issue 1 (13th March 2017) - Trundle, Grace; Craig, Leam A.; Stringer, Ian
Abstract : Purpose: The purpose of this paper is to explore the different clinical features of pathological demand avoidance (PDA) and antisocial personality disorder (ASPD) presented in the form of a single case study. The study highlights the potential of misdiagnosis and conceptual confusions to practitioners in forensic settings between the two conditions when working with offenders with personality disorders. Design/methodology/approach: A case formulation using the "five Ps" method based on the personal history of an incarcerated male is presented and the clinical similarities and differences between PDA and ASPD are delineated. These differences and similarities are evaluated and applied to offender management including intervention options. Findings: There are considerable similarities between ASPD and PDA making the two conditions difficult to separate. Both diagnostic criteria identify childhood behavioural problems, aggression, destructiveness, conduct disorder (CD), manipulation and non-compliance as indications of the disorder. For example, the criteria for later adult ASPD are the presence of childhood antisocial behaviour and CD. However, these behaviours may also be suggestive of the attention deficit hyperactivity disorder and non-compliance that are part of PDA. Violent behaviours and aggression can also be perceived in a similar way. Misdiagnosis of PDA as ASPD reduces the efficiency of treatment programmes. Originality/value: The implications of these findings could prove useful in the successful risk management of offenders with PDA. Given the similar behavioural characteristics between PDA and ASPD, the prevalence of PDA among offenders may be higher than observed. The aim of this study is to raise awareness of potential conceptual complications and clinical confusions between the two conditions with a view to aid offender management through case formulation. A large scale study into offenders with PDA would draw attention to the prevalence of the condition as well as its association with offending behaviour.